Mild Cognitive Disorders are Associated with Different Patterns of Brain asymmetry than Normal Aging: The PATH through Life Study - Cherbuin, Nicolas; Réglade-Meslin, Chantal; Kumar, Rajeev; Sachdev, Perminder; Anstey, Kaarin J. (Frontiers in Psychiatry, 2010)
Background and Purpose: Defining how brain structures differ in pre-clinical dementia is important to better understand the pathological processes involved and to inform clinical practice. The aim of this study was to identify significant brain correlates (volume and asymmetry in volume) of mild cognitive disorders when compared to normal controls in a large community-based sample of young-old individuals who were assessed for cognitive impairment. Methods: Cortical and sub-cortical volumes were measured using a semi-automated method in 398 participants aged 65-70 years who were selected from a larger randomly sampled cohort and who agreed to undergo an MRI scan. Diagnoses were reached based on established protocols for MCI and a more inclusive category of any Mild Cognitive Disorder (any-MCD: which includes AAMI, AACD, OCD, MNC, CDR, MCI). Logistic regression analyses were used to assess the relationship between volume and asymmetry of theoretically relevant cerebral structures (predictors) and MCI or any-MCD while controlling for age, sex, and intra-cranial volume. Results: The main correlates of cognitive impairment assessed in multivariate analyses were hippocampal asymmetry (more to left, MCI: OR 0.83, 95%CI 0.71-0.96, p = .013; MCD: OR 0.86, 95%CI 0.77-0.97, p = .011), lateral ventricle asymmetry (more to left, MCI: OR 0.95, 95%CI 0.91-0.99, p = .009; MCD: OR 0.95, 95%CI 0.92-0.98, p = .004), and cerebellar cortex asymmetry (more to left, MCI: OR 1.51, 95%CI 1.13-2.01, p = .005). Conclusions: In this population-based cohort stronger associations were found between asymmetry measures, rather than raw volumes in cerebral structures, and mild cognitive disorders.